1995
DOI: 10.1002/jmri.1880050405
|View full text |Cite
|
Sign up to set email alerts
|

A segmented k‐space velocity mapping protocol for quantification of renal artery blood plow during breath‐holding

Abstract: Two important prerequisites for MR velocity mapping of pulsatile motion are synchronization of the sequence execution to the time course of the flow pattern and robustness toward loss of signal in complex flow fields. Synchronization is normally accomplished by using either prospective ECG triggering or so-called retrospective gating. However, if the studied vessel moves periodically in space as a result of respiratory motion, as in the case of renal arteries, a second synchronization with respect to the vesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 20 publications
3
21
0
1
Order By: Relevance
“…Consequently, the acquisi tion can be performed in seconds instead of min utes, with high temporal and spatial resolution [60][61][62][63][64]. If velocity-encoding gradients are added to the regular sequence, the flow velocity can be measured rapidly.…”
Section: Rapid Magnetic Resonance Phase Velocity Mappingmentioning
confidence: 99%
“…Consequently, the acquisi tion can be performed in seconds instead of min utes, with high temporal and spatial resolution [60][61][62][63][64]. If velocity-encoding gradients are added to the regular sequence, the flow velocity can be measured rapidly.…”
Section: Rapid Magnetic Resonance Phase Velocity Mappingmentioning
confidence: 99%
“…Respiratory motion, which causes the renal arteries to move during data acquisition, appears to be a considerable source of error in these measurements [20,21,22]. Synchronization with respect to respiratory motion, along with cardiac triggering, seems to be necessary to obtain accurate, reproducible flow data [22,23].…”
Section: Introductionmentioning
confidence: 98%
“…TGE has shown better flow behavior and is, therefore, more promising for reliable ultrafast flow quantification with relatively disturbed flow and significant vessel motion (e.g., coronary arteries). 9,10,14,20,25 In addition, previous in vitro and clinical studies 2,10,11,14,19,20,23,25,28,29 evaluating both EPI and TGE techniques for PVM have indicated that TGE is generally superior in terms of temporal and (sub-millimeter…”
Section: Introductionmentioning
confidence: 99%